A CASE-STUDY OF THE MOLECULAR DIAGNOSIS OF ECHINOCOCCUS MULTILOCULARIS IN WILD BOAR WITH COMMENTS ON ITS PUBLIC HEALTH SIGNIFICANCE IN TURKEY - Kesik, Harun Kaya; Kilinc, Seyma Gunyakti; Celik, Figen; Simsek, Sami; Ahmed, Haroon (Knowledgeworks Global Ltd-Kgl, 2020)
Echinococcus multilocularis is a parasite species of zoonotic importance which can be fatal to humans and causes Alveolar Echinococcosis (AE). This report describes the development of a cyst from the liver of a wild boar and molecular confirmation of its identification. The cyst material was obtained from the liver of a wild boar killed by hunters. Genomic DNA was extracted from the germinal layer of the cyst material, and 875 bp mitochondrial cytochrome c oxidase subunit I (COI) gene fragment was amplified by PCR and sequenced. A BLAST search matched 100% with published Echinococcus multilocularis sequences. This study confirms the occurrence of E. multilocularis in a wild boar for the first time in Turkey.
Keywords: Echinococcus multilocularis; Wild Boar; PCR; Sequencing; Turkey